Downregulation of Nrf2 by the combination of TRAIL and Valproic acid induces apoptotic cell death of TRAIL-resistant papillary thyroid cancer cells via suppression of Bcl-xL. Issue 1 (1st March 2016) - Cha, Hyun-Young; Lee, Bok-Soon; Chang, Jae Won; Park, Ju Kyeong; Han, Jae Ho; Kim, Yong-Sung; Shin, Yoo Seob; Byeon, Hyung Kwon; Kim, Chul-Ho
Highlights: The underlying mechanism of co-treatment of TRAIL and VPA was investigated. VPA sensitized TRAIL-resistant thyroid cancer (PTC) cells to apoptotic cell death. Combination of TRAIL and VPA induces apoptosis by downregulation of Bcl-xL and Nrf2. Combination treatment suppresses tumor progression in an orthotopic PTC model. Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) represents an effective agent for the treatment of many cancers, though the majority of thyroid cancers are found to be resistant. Therefore it would be necessary to identify agents capable of increasing the sensitivity of these cancers to TRAIL-mediated cell death. Here, we examined the therapeutic effect and its underlying mechanism of combination treatment of TRAIL and histone deacetylase inhibitor, Valproic acid (VPA) in vitro using human papillary thyroid cancer (PTC) cells and in vivo using an orthotopic mouse model of PTC. TRAIL-VPA combination therapy synergistically induced apoptotic cell death in TRAIL-resistant PTC through caspase activation. In addition, downregulation of antioxidant transcription factor, Nrf2 by co-treatment of TRAIL-VPA induces cell death via suppression of Bcl-xL in vitro and in vivo ; these effects were further enhanced following siRNA inhibition of these proteins in combination with TRAIL or TRAIL-VPA. Taken together, VPA sensitized TRAIL-resistant PTC cells to apoptotic cell death through involvement of Nrf2 and Bcl-xL. Thus, the combination of VPA and TRAIL may be a promising therapy for TRAIL-resistant PTC.